2011
DOI: 10.5209/rev_sjop.2011.v14.n1.33
|View full text |Cite
|
Sign up to set email alerts
|

Predictors of the Pain Perception and Self-Efficacy for Pain Control in Patients with Fibromyalgia

Abstract: Objective: This study analyzes the role of a number of cognitive-affective dimensions in the experience and coping of pain in patients with fibromyalgia (FM). Specifically, it was examined whether anxiety, depression, pain catastrophizing and pain-related anxiety predict the pain perception and the self-efficacy expectations in these patients.Method: Seventy-four fibromyalgia patients were asked to complete a questionnaire survey including theChronic Pain Self-Efficacy Scale, theHospital Anxiety and Depression… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
33
2
1

Year Published

2013
2013
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 47 publications
(37 citation statements)
references
References 24 publications
1
33
2
1
Order By: Relevance
“…However, there is considerable co-linearity between symptoms of anxiety and depression [217,265,266], and several investigations show both to be associated with pain, sleep disturbances, symptom severity, poorer perceived health, worse physical function, decreased vitality, and impaired social function [217,234,265,266,268]. In yet another investigation, both depression and anxiety scores correlated with the sensory and affective components of the MPQ and with pain intensity, but in regression analyses, only the physiological component of anxiety together with helplessness and fear of pain predicted the various aspects of pain, whereas depression was an important component in predicting self-efficacy for pain management and coping with symptoms [89]. Similarly, the presence of PTSD in FMS patients is associated with more severe symptoms (more pain, tenderness, and distress, and greater functional impairment) [245, 247], while FMS has a similar effect on PTSD [248, 249], although that is not an entirely consistent finding [244].…”
Section: Correlations Between Depression Anxiety and Fms Symptomsmentioning
confidence: 98%
See 1 more Smart Citation
“…However, there is considerable co-linearity between symptoms of anxiety and depression [217,265,266], and several investigations show both to be associated with pain, sleep disturbances, symptom severity, poorer perceived health, worse physical function, decreased vitality, and impaired social function [217,234,265,266,268]. In yet another investigation, both depression and anxiety scores correlated with the sensory and affective components of the MPQ and with pain intensity, but in regression analyses, only the physiological component of anxiety together with helplessness and fear of pain predicted the various aspects of pain, whereas depression was an important component in predicting self-efficacy for pain management and coping with symptoms [89]. Similarly, the presence of PTSD in FMS patients is associated with more severe symptoms (more pain, tenderness, and distress, and greater functional impairment) [245, 247], while FMS has a similar effect on PTSD [248, 249], although that is not an entirely consistent finding [244].…”
Section: Correlations Between Depression Anxiety and Fms Symptomsmentioning
confidence: 98%
“…Their unpredictability along with the difficulty of family, friends and physicians to accept the reality of these symptoms are in themselves further sources of stress and distress for FMS patients. Other factors that strongly influence pain perception are coping styles, in particular catastrophizing and having an external locus of control, which positively correlate with pain and other symptoms, while self-efficacy is associated with reduced pain perception [87][88][89][90].…”
Section: The Symptoms and Some Of Their Objective Correlates Pain Andmentioning
confidence: 98%
“…Chronic pain and depression increase the risk of suicide (Barkin et al, 2011;Calandre et al, 2011). Social support and family self-efficacy moderate the relationship between family problems and depression in patients with FM (Libby & Glenwick, 2010), and support from a closer social network reduces anxiety and depression, and, therefore, also helps relieve pain (Salgueiro et al, 2009;Sanchez, Martinez, Miro, & Medina, 2011).…”
Section: Introductionmentioning
confidence: 97%
“…Although the historical consensus has been that depression facilitates or amplifies the perception of pain (21,22), new evidence favors situations in which depression is associated with a reduced perception of experimental pain (23). For example, in a complex meta-analysis of depression and pain perception, Dickens and colleagues (24) concluded that depression was associated with higher pain thresholds (rather than lower pain thresholds that would facilitate pain) and attributed that finding to inattention.…”
Section: Mini International Neuropsychiatric Interview Depressiomentioning
confidence: 99%